2018
DOI: 10.1175/jcli-d-17-0090.1
|View full text |Cite
|
Sign up to set email alerts
|

Variability and Confidence Intervals for the Mean of Climate Data with Short- and Long-Range Dependence

Abstract: This paper presents an adaptive procedure for estimating the variability and determining error bars as confidence intervals for climate mean states by accounting for both short- and long-range dependence. While the prevailing methods for quantifying the variability of climate means account for short-range dependence, they ignore long memory, which is demonstrated to lead to underestimated variability and hence artificially narrow confidence intervals. To capture both short- and long-range correlation structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…A key issue in our study and in trend significance assessments is whether observed low-frequency natural variability should be estimated after signal removal or from raw data. 7 One scientific perspective is that the latter strategy is preferable (Franzke 2010(Franzke , 2012aBowers and Tung 2018). This is not an unreasonable strategy when dealing with climate data at individual locations, where the true signal is poorly known and S/N ratios are lower than for global-scale spatial averages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key issue in our study and in trend significance assessments is whether observed low-frequency natural variability should be estimated after signal removal or from raw data. 7 One scientific perspective is that the latter strategy is preferable (Franzke 2010(Franzke , 2012aBowers and Tung 2018). This is not an unreasonable strategy when dealing with climate data at individual locations, where the true signal is poorly known and S/N ratios are lower than for global-scale spatial averages.…”
Section: Discussionmentioning
confidence: 99%
“…The indices p and q are the orders of the autoregressive and moving-average components of the model, respectively. The simplest FARIMA(0, d, 0) model has been used to describe a slowly decaying temporal autocorrelation structure in studies of long-term climate variability and trend significance (Bloomfield and Nychka 1992;Koscielny-Bunde et al 1998;Franzke 2012a,b;Imbers et al 2014;Franzke et al 2015;Bowers and Tung 2018).…”
Section: Statistical Models Of Observed Variabilitymentioning
confidence: 99%
“…Moreover, because long-term records of environmental variables show often long-range memory, some other tools are usually applied. The fractionally integrated moving average models [ARFIMA (p,d,q)] have been widely used in the literature to describe meteorological variables (Yaya and Fashae, 2015;Bowers and Tung, 2018), pollutants and soil gas (Pan and Chen, 2008;Donner et al, 2015;Belbute and Pereira, 2017;Reisen et al, 2018), and hydrological time series (Montanari et al, 1997;Wang et al, 2007). This class of models is used when the longterm correlations in the data decay more slowly than an exponential form, that is, a typical shape of autocorrelation in the autoregressive moving average [ARMA(p,q)] processes (Box et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Confidence intervals (CIs) were obtained from the values of the adjusted variables using the Student's t test (α = 0.95). Considering that the CIs in the climatology are a useful resource for the identification of similar climates(Mudelsse, 2013;Bowers and Tung, 2018), and due to the existence of different microclimates in each region, if the values of temperature and precipitation extracted from the isohypsa of RESO were within the CIs determined by the group of stations, they would represent similarity conditions with a confidence level of 95%.…”
mentioning
confidence: 99%